Persepsi VisualPengunjung terhadap Elemen Interior Stilrod CafÃ© di Surabaya - Siswanto, Cynthia (Intra, 2015)
This research about visual perception of British Interior-styled cafÃ© at Surabaya aims to perceivehow the visual perception occurred while researcher in the thematic cafÃ© through their applied interior design. This research was conducted in Surabaya with a case study of Stilrod CafÃ©Â  as British Interior Design cafÃ©. Qualitative-descriptive type research method is used in this research. Thecompiling data, literature-checking, interviews and direct observation to the object are necessary,whichthen followed by data analysis method then deduced into a conclusion. Results of the research become a case study of one thematic-British Interior Design-cafÃ© style in Surabaya. Through this research, it is known how the customerâs visual perception about interior design of Stilrod CafÃ©.